Chapter Makeup and marquinha: aesthetics of the bodily surface in Rio de Janeiro - Novacich, Samuel (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
This chapter focuses on two aesthetic practices on the urban periphery of Rio de Janeiro, Brazil. First, I discuss applications of bright, deliberately eye-catching makeup in the context of professional makeup salons, among amateur enthusiasts, and in relation to women's empowerment classes at a community center in a small favela located in Rio's downtown. Second, I describe a tanning practice known as marquinha (little mark), in which strips of tape are applied to the body and used to create precise tan lines. Taking as a starting point the assertion that aesthetics and political dynamics are inextricably entwined, I draw comparisons between these aesthetic practices and their relation to questions of sexuality and desire, power and self-empowerment, and to questions of race. In Rio de Janeiro, as elsewhere, aesthetics are particularly important to the politics of inequality that define the urban landscape. And while aesthetics may often express ideas and indeed "say something" about their practitioners, they are hardly just passive reflections of society. This chapter focuses instead on the pragmatic power of makeup and marquinha to "causar" (to cause) and make real material impacts on viewers. In describing these practices as pragmatic, I call attention to aesthetics as a relational practice that mediates between the self and other, and invites new social possibilities. As such, makeup and marquinha are understood as co-constitutive of the contexts within which they are found, shaping not only relations between individuals and things, but also, one's understanding of the self.